Analisis penghambatan aktivitas mortalin dengan senyawa herbal Indonesia untuk skrening anti kanker melalui in silico - UB, Widodo (Prosiding KPSDA, 2015)
The prevalence of cancer in Indonesia is still very high, especially breast and cervical cancer. However, the potent and safe drugs for cancer therapy are still not available. One strategy to find the safe cancer drug is screening active compound that able to block the function of mortalin protein. In cancer cells, mortalin inhibits p53 protein to enter the nucleus, which inhibit p53 function to stimulate apoptosis and cell cycleÂ arrest in cancer cells. In this study, mortalin is used as target protein to screen of active compounds from Indonesia plants. The active compounds were analysed its binding affinity to p53-binding domains of mortalin, compared to withanone as a positive control. The result suggested that four compounds, there are Hesperidin, Artoindonesianin A, glycyrrhetinic acid, and Liriodenine have better binding affinity to mortalin compared to withanone. These compounds can be isolated from Citrus aurantium, Artocarpus reticulatus, Glycyrrhiza glabra and Michelia champaca, respectively. Therefore by using the active compound as cancer drug material will preserve the plant in the nature.